Persistent candidemia despite appropriate fungal therapy: First case of Candida auris from the United Arab Emirates. (May 2018) - Alatoom, Adnan; Sartawi, Mohammad; Lawlor, Karen; AbdelWareth, Laila; Thomsen, Jens; Nusair, Ahmad; Mirza, Imran
Highlights: Candida auris is an emerging multi-drug resistant and health-care associated candida species. This case reports the first case of Candida auris infection from the United Arab Emirates. Microbiology laboratories should be aware that Candida auris maybe misidentified by conventional identification systems and confirmation is necessary in suspected cases. Abstract: In this case, we report an elderly patient with multiple chronic conditions and prolonged intensive care unit (ICU) stays who had recurrent Candida auris ( C. auris ) in blood despite antifungal therapy. C. auris was misidentified using conventional automated identification system as Candida haemulonii resulting in delayed diagnosis. The isolate showed increasing minimum inhibitory concentrations (MICs) to different antifungal drugs and persisted in the patient's blood before the patient deceased. This is the first case of C. auris reported from the United Arab Emirates (UAE); laboratories should be aware of this Candida species and should confirm suspected cases since it is an emerging multi-drug resistant and health-care associated Candida .